Optimizing the Use of Technology in Payment Systems and Its Implications for the Digital Financial Sector - Soni Suardi; Yulianti; Jacky Chin; Budi Margono (PT. Anagata Sembagi Education, 2024)
This study aims to analyze the influence of the use of technology in payment systems on the development of the digital financial sector, as well as the challenges faced in optimizing these technologies. Using a quantitative approach and explorative-descriptive research methods, this study collected data from 210 respondents of active users of digital payment services through a questionnaire survey. The results show that digital payment technologies, such as e-wallets, QRIS, and blockchain, contribute significantly to transaction efficiency and security, as well as accelerating the growth of the digital financial sector and improving financial inclusion. On the other hand, challenges such as cyber threats, digital infrastructure inequality, and low digital literacy are still major barriers to technology optimization. Adaptive government regulation and collaboration between the fintech and banking sectors are needed to create a more inclusive and sustainable payments ecosystem. The conclusion of this study is that the optimization of payment technology is essential to drive digital transformation in the financial sector, and efforts to address existing challenges must be carried out jointly between governments, industry players, and the public. This research provides important insights for policy makers and industry players to design strategies that support the development of the digital financial sector.